Assessment of plant diversity in homegardens of rural and urban areas of Tripura, North-East India - Das, Sumit Kumar; Deb, Sourabh; Debnath, Bimal (Indian Journal of Agroforestry, 2020)
Present investigation was aimed to study the structural composition and functional diversity of homegardens (HGs) in the rural and semi-urban/ urban areas of Tripura, the North-Eastern state of India. The work involved plant species inventories in 64 HGs. A total of 117 species in 50 families were recorded. Fabaceae was the most diversified family, followed by Malvaceae and Solanaceae. In the urban areas, HGs were mostly subsistence type (88.89%) while in rural areas, 63.04% of HGs were of intermediate type. Both the HGs showed vertical as well as horizontal complexity in species diversity. Dominance distribution curve showed the negative effect of the urbanization and changes in socio-economic status on HGs practices and agro-biodiversity conservation. Rural HGs are characterized with rich compositional, structural and functional diversity and playing significant roles for in-situ conservation, securing environmental health and also providing livelihood support.